PENINGKATAN KUALITAS WARMER STERNO JELLY DENGAN METODE TAGUCHI - Ahmad, Anton Royanto; Budiyanto, Aris; Mu’alif, Fazar; Widodo, Slamet (AME (Aplikasi Mekanika dan Energi): Jurnal Ilmiah Teknik Mesin, 2018)
Alternative fuel will be one of the solutions for resolving energy crisis that happening now. Methanol gel is one of them that have lot of benefits. In this paper will be discussing how to increase quality of methanol gel. The quality that we pursue is to decrease number of explosion when the process of incineration was executed. Only four factors observed in this study, include; using purple dye, number of NCl volume, number of layer, and using water as raw material. Experiment method used in this study was Taguchi Method with L8 orthogonal array and twice repetitions. The results that we get were quite surprising. Using ANOVA with 95% level of confidence as analyzer the results, show us that the influencing factors for methanol gel quality were using purple dye, number of layer, and using water.